The stress analysis in electric poles with CFRP to prevent the consecutive demolishing from car accidents - Suchat Suvimolwan; Atavit Sujaritpong (My University, 2018)
In statistically accidental reports, we could find progressive collapse of prestressed concrete electric poles from car accident, this is due to the poor properties of concrete which limits the impact resistance, the failure will therefore occur in the position of impact where maximum stress is presented near the base. The weight of broken concrete at above the failure position will cause the impact force to the adjacent electric poles, resulting in consecutive damage and increase the tensile force in electric cables. This research will emphasize repositioning of failure at pole base by application of CFRP material. Finite element analysis will be introduced to analyse the thickness of CFRP in order to control the desired point of failure. The result can be a guideline to prevent the consecutive demolishing for the existing electric poles later on.
Keywords: Accidental; Position (finance); Base (topology); Prestressed concrete; Structural Response to Dynamic Loads